PENGARUH UKURAN PERUSAHAAN, LISTING AGE, DAN LEVERAGE TERHADAP INTELLECTUAL CAPITAL DISCLOSURE - Hana, Tri Selomita; Suzan, Leny (LPPM Universitas Bina Bangsa, 2025)
This study aims to investigate the impact of factors such as company size, listing age, and leverage on the disclosure of intellectual capital in the food and beverage (F&B) sub-sector, both simultaneously and partially listed on the Indonesia Stock Exchange (IDX), during the 2018-2022 period. This study examines companies in the food and beverage sub-sector listed on the IDX from 2018 to 2022. We used purposive sampling to collect data from 17 companies and 85 observation data points. This study found that factors such as company size, listing age, and leverage simultaneously affect intellectual capital disclosure. Firm size has a partial positive impact on intellectual capital disclosure, while listing age and leverage have a negative impact.